Perancangan Media Pembelajaran Biologi Kelas XI Menggunakan Heyzine untuk Meningkatkan Konsentrasi Belajar Siswa - Kurnia Putri, Silvy; Annas , Firdaus (Yayasan Lembaga Studi Makwa, 2024)
Advances in technology and information in the era of the industrial revolution 4.0 require teachers to be able to create interactive media that can help the learning process at school. Based on observations and interviews conducted at SMAN 3 Sawahlunto, the learning process still uses power point, LKPD and the internet as learning resources that are not can fully support students' learning, they cannot help and understand students' lessons in class so that it has an impact on student learning outcomes. The aim of this research is to design an e-module as a Biology learning media using the Hyzine application which is valid, practical and effective to help teachers in delivering learning so that it makes it easier for students to understand the lesson and improve student learning outcomes. This research model uses the R&D method with the ADDIE model. The result of this research is the formation of a biology learning media in the form of an e-module that can be accessed using a cellphone with internet access. This e-book can be used by students to study anywhere and anytime. This media product has been tested through validation by two computer experts and one language expert with a score of 0.87 in the valid category. The results of the practicality test with two teachers at SMAN 3 Sawahlunto obtained a score of 0.91 with a very high practicality level category and the results of the effectiveness test with 20 class XI female students obtained a score of 0.79 with the effective category. Researchers have succeeded in designing biology learning media in the form of e-modules using the Hyzine application which it is hoped can be used to help the learning process in class XI and can improve student learning outcomes. Abstrak Kemajuan teknologi dan informasi diera revolusi industry 4.0 menuntut guru untuk dapat menciptakan media yang interaktif yang dapat membantu proses pembelajaran disekolah. Berdasarkan observasi dan wawancara yang dilakukan di SMAN 3 Sawahlunto, dalam proses pembelajaran masih menggunakan power point, LKPD dan internet sebagai sumber belajar yang tidak dapat sepenuhnya menunjang pelajaran siswa, tidak bisa membantu dan memahami pelajaran siswa di kelas sehingga berdampak kepada hasil belajar siswa. Tujuan dari penelitian ini untuk merancang sebuah e-modul sebagai media pembelajaran Biologi menggunakan aplikasi Hyzine yang valid, praktis dan efekti untuk dapat membantu guru dalam menyampaikan pembelajaran sehingga memudahkan siswa untuk memahami pelajaran dan meningkatkan hasil belajar siswa. Model penelitian ini menggunakan metode R&D dengan model ADDIE. Hasil penelitian ini adalah terbentuknya sebuah media pembelajaran biologi berupa e-modul yang dapat di akses menggunakan handphone dengan akses internet. E-book ini dapat di gunakan oleh siswa untuk belajar dimana dan kapan saja. Produk media ini telah diuji melalui validasi oleh dua orang ahli komputer dan satu orang ahli bahasa dengan perolehan nilai 0,87 dengan kategori valid. Hasil uji praktikalitas dengan dua orang guru SMAN 3 Sawahlunto diperoleh nilai 0,91 dengan kategori tingkat kepraktisan sangat tinggi dan hasil uji efejtivitas dengan 20 orang siswa siswi kelas XI di peroleh nilai 0,79 dengan kategori efektif. Peneliti sudah berhasil merancang media pembelajaran biologi berupa e-modul menggunakan aplikasi Hyzine yang diharapkan dapat digunakan membantu proses pembelajaran di kelas XI dan dapat meningkatkn hasil belajar siswa.